The SOLIDS 6G Mobile Network Architecture: Driving Forces, Features, and Functional Topology. (January 2022) - Liu, Guangyi; Li, Na; Deng, Juan; Wang, Yingying; Sun, Junshuai; Huang, Yuhong
Abstract: With the large-scale commercial launch of fifth generation (5G) mobile network, the development of new services and applications catering to the year 2030, along with the deep convergence of information, communication, and data technologies (ICDT), and the lessons and experiences from 5G practice will drive the evolution of the next generation of mobile networks. This article surveys the history and driving forces of the evolution of the mobile network architecture and proposes a logical function architecture for sixth generation (6G) mobile network. The proposed 6G network architecture is termed SOLIDS (related to the following basic features: soft, on-demand fulfillment, lite, native intelligence, digital twin, and native security), which can support self-generation, self-healing, self-evolution, and self-immunity without human involvement and address the primary issues in the legacy 5G network (e.g., high cost, high power consumption, and highly complicated operation and maintenance), significantly well.